2021
DOI: 10.3390/horticulturae7110440
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ecklonia maxima Extracts on Growth, Yield, and Postharvest Quality of Hydroponic Leaf Lettuce

Abstract: Ecklonia maxima is a brown algae seaweed largely harvested over the last years and used to produce alginate, animal feed, fertilizers, and plant biostimulants. Their extracts are commercially available in various forms and have been applied to many crops for their growth-promoting effects which may vary according to the treated species and doses applied. The aim of the study was to characterize the effect of adding an Ecklonia maxima commercial extract (Basfoliar Kelp; 0, 1, 2, and 4 mL L−1) to the nutrient so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 103 publications
2
11
1
Order By: Relevance
“…1; Tables 2 and 3). In contrast to our findings, Cristofano et al (2021a) and Miceli et al (2021) reported increases in growth and yield of hydroponic lettuce plants treated with hydrolyzed proteins and seaweed extracts, respectively, compared with untreated control plants. However, both studies were conducted in a greenhouse where daily temperatures reached up to 34 to 36 C. Considering that lettuce has an optimal day/night temperature close to 24/19 C (Choi et al, 2000;Seginer et al, 1991), the positive effects found in those studies are plausibly attributed to a heat stress tolerance advantage provided by the biostimulant treatments.…”
Section: Resultscontrasting
confidence: 99%
“…1; Tables 2 and 3). In contrast to our findings, Cristofano et al (2021a) and Miceli et al (2021) reported increases in growth and yield of hydroponic lettuce plants treated with hydrolyzed proteins and seaweed extracts, respectively, compared with untreated control plants. However, both studies were conducted in a greenhouse where daily temperatures reached up to 34 to 36 C. Considering that lettuce has an optimal day/night temperature close to 24/19 C (Choi et al, 2000;Seginer et al, 1991), the positive effects found in those studies are plausibly attributed to a heat stress tolerance advantage provided by the biostimulant treatments.…”
Section: Resultscontrasting
confidence: 99%
“…The results of the present in-vestigation show that the treatments without stress showed a greater stomatal conductance. Similar results were reported by Miceli et al [48], indicating that the use of extracts of Ecklonia maxima in lettuce cultivation increased stomatal conductance at all concentrations (1, 2, and 4 mL L −1 ) compared to the control. The results are because brown algae extracts contain osmolytes such as proline, glycine betaine, and carbohydrates, compounds that allow for osmotic adjustment and that facilitate the absorption of water and nutrients by plants [49][50][51].…”
Section: Stomatal Conductancesupporting
confidence: 90%
“…can be used as liquid organic fertilizer. Research by Miceli et al (2021) showed that Ecklonia maxima is a brown algae seaweed between 2 and 4 ml l −1 , enhanced plant growth and improved the yield and many morphological and physiological traits of lettuce. The results showed that the treatment of organic nutrient solutions could not match the quality of AB mix hydroponic nutrient solutions as hydroponic nutrients for mustard plant cultivation.…”
Section: Resultsmentioning
confidence: 99%